MOVABLE CONTACT CONFIGURED TO BE INTEGRATED INTO A CIRCUIT BREAKER - PUH, Nikola; ELOY, Stéphane; KETTERER, Olivier (2024)
The subject of the present invention relates to a movable contact configured to be integrated into a circuit breaker and bearing against a fixed contact in the vicinity of an arc extinguishing chamber, the movable contact having the form of a plurality of fingers (2) juxtaposed in a substantially parallel manner and aligned with one another and joined by one of their ends (2a) to a common trunk, characterized in that the inter-digital spaces separating the respective surfaces of two juxtaposed fingers (2) of the movable contact have a spacing width with a value equal to or less than 1.3 millimetres.